The LEGO Mindstorms robot inventor activity book : a beginner's guide to building and programming LEGO robots - Benedettelli, Daniele, 1984- (No Starch Press, 2021)
An introduction to the LEGO Mindstorms Robot Inventor Kit through seven engaging projects. With its amazing assortment of bricks, motors, and smart sensors, the LEGO® MINDSTORMS® Robot Inventor set opens the door to a physical-meets-digital world. The LEGO MINDSTORMS Robot Inventor Activity Book expands that world into an entire universe of incredibly fun, uniquely interactive robotic creations! Using the Robot Inventor set and a device that can run the companion app, you'll learn how to build bots beyond your imagination--from a magical monster that gobbles up paper and answers written questions, to a remote-controlled transformer car that you can drive, steer, and shape-shift into a walking humanoid robot at the press of a button. Author and MINDSTORMS master Daniele Benedettelli, a robotics expert, takes a project-based approach as he leads you through an increasingly sophisticated collection of his most captivating robot models, chapter by chapter. Each project features illustrated step-by-step building instructions, as well as detailed explanations on programming your robots through the MINDSTORMS App--no coding experience required. As you build and program an adorable pet turtle, an electric guitar that lets you shred out solos, a fully functional, whiz-bang pinball machine and more, you'll discover dozens of cool building and programming techniques to apply to your own LEGO creations, from working with gears and motors, to smoothing out sensor measurement errors, storing data in variables and lists, and beyond. By the end of this book, you'll have all the tools, talent and inspiration you need to invent your own LEGO MINDSTORMS robots.